2018
DOI: 10.1186/s12935-018-0642-8
|View full text |Cite
|
Sign up to set email alerts
|

miR-506 attenuates methylation of lncRNA MEG3 to inhibit migration and invasion of breast cancer cell lines via targeting SP1 and SP3

Abstract: BackgroundBreast cancer has been the first death cause of cancer in women all over the world. Metastasis is believed to be the most important process for treating breast cancer. There is evidence that lncRNA MEG3 functions as a tumor suppressor in breast cancer metastasis. However, upstream regulation of MEG3 in breast cancer remain elusive. Therefore, it is critical to elucidate the underlying mechanism upstream MEG3 to regulate breast cancer metastasis.MethodsWe employed RT-qPCR and Western blot to examine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Our data shows that, in the absence of CCDC26, genome is hypomethylated which leads to increase in apoptosis and DNA damage, and cell growth inhibition. In the past, non-coding RNAs have been shown to impact DNA methylation levels through transcriptional and post-transcriptional regulation of DNMT genes Wang, Guo, et al 2018;Cheng et al 2018;Mohammad et al 2010;Di Ruscio et al 2013;Merry et al 2015). However, unlike many previous publications, DNMT expression levels were unchanged in CCDC26 KOs, indicating that the mechanism behind the observed DNA hypomethylation is different.…”
Section: Discussionmentioning
confidence: 70%
“…Our data shows that, in the absence of CCDC26, genome is hypomethylated which leads to increase in apoptosis and DNA damage, and cell growth inhibition. In the past, non-coding RNAs have been shown to impact DNA methylation levels through transcriptional and post-transcriptional regulation of DNMT genes Wang, Guo, et al 2018;Cheng et al 2018;Mohammad et al 2010;Di Ruscio et al 2013;Merry et al 2015). However, unlike many previous publications, DNMT expression levels were unchanged in CCDC26 KOs, indicating that the mechanism behind the observed DNA hypomethylation is different.…”
Section: Discussionmentioning
confidence: 70%
“…Silencing DNMT1 inhibits the proliferation, migration and invasion of breast cancer cells by promoting the expression of MEG3 through demethylation Current studies have found that lncRNA MEG3 is regulated by DNMT1, and the promoter of MEG3 is methylated under the in uence of DNMT1, while MEG3 appears to be hypermethylated and lowly expressed in tumors 9,15,17 . We further examined the effect of the interaction of MEG3 and DNMT1 on the breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant methylation promoted by DNMT1 can increase the drug resistance of breast cancer cells to anticancer drugs. DNMT1 also promotes the development of breast cancer by reducing the expression of MEG3 9 . Therefore, this study veri ed the role of DNMT1 in regulating MEG3, and the results were consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In recent years, the incidence of breast cancer is increasing. [4][5][6] However, the pathogenesis of breast cancer remains unclear. 7 Accumulating evidence have shown that lncRNAs exert important roles in the progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%